2006
DOI: 10.1182/asheducation-2006.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Managing Imatinib Resistance

Abstract: While imatinib is highly effective therapy, with improving prospects over time for sustained remission and potential to severely limit or eliminate disease progression and transformation, a minority of patients either fail or respond suboptimally to imatinib; as well, disease eradication may not be possible with imatinib. Distinct patterns of resistance have evolved with the use of imatinib, and Abl kinase mutations, which alter imatinib binding or favor kinase conformations inaccessible to imatinib, are a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…In patients receiving Imatinib for chronic myelogenous leukemia, for example, resistance emerges often [49]. Further understanding of the mechanisms involved in drug resistance will be crucial to the effective treatment of patients with MTC.…”
Section: Ongoing Challenges and Unmet Needsmentioning
confidence: 99%
“…In patients receiving Imatinib for chronic myelogenous leukemia, for example, resistance emerges often [49]. Further understanding of the mechanisms involved in drug resistance will be crucial to the effective treatment of patients with MTC.…”
Section: Ongoing Challenges and Unmet Needsmentioning
confidence: 99%
“…[8][9][10] In an attempt to overcome imatinib resistance, 2 nd -generation tyrosine kinase inhibitors were developed, including dasatinib, nilotinib, bosutinib, and ponatinib. [11][12][13][14] However, the costs of 2nd-generation tyrosine kinase inhibitors may be prohibitive, particularly in emerging regions such as the Asia-Pacific countries, and new, lower cost alternatives are necessary. [15][16][17][18] Radotinib (Supectℱ; C27H21F3N8OHCl, 4-Methyl-N-[3-(4-methyl-imidazol-1-yl)-5-trifluoromethyl-phenyl]-3-(4-pyrazin-2-yl-pyrimidin-2-ylamino)-benzamide hydrochloride; IL-YANG Pharm.…”
Section: Introductionmentioning
confidence: 99%
“…4). One study demonstrated that even a two-fold increase in fusion transcript levels was tightly associated with the presence of mutations [53]; current recommendations suggest that a 5-to 10-fold increase in levels might prompt mutation testing [39]. A variety of different technologies are available to identify and quantify KD mutations and include [herein listed from least sensitive (15-25%) to most sensitive (0.01%)]: direct sequencing, subcloning and sequencing, denaturing high-performance liquid chromatography (DHPLC), pyrosequencing, and allele-specific oligonucleotide PCR.…”
Section: Imatinib Resistancementioning
confidence: 99%
“…Primary resistance is defined as the failure to achieve an initial response to therapy and is seen in only 5% of newly diagnosed patients in chronic phase CML [39]. Mechanistically, primary resistance is typically BCR-ABL1 independent [40].…”
Section: Imatinib Resistancementioning
confidence: 99%
See 1 more Smart Citation